Abstinence symptoms after withdrawal of tranquillising drugs: is there a common neurochemical mechanism? - Cowen, P; Nutt, D (1982)
Withdrawal of anxiolytic agents such as ethanol, barbiturates, and benzodiazepines may result in a syndrome characterised in its most severe form by delirium and seizures. There is increasing evidence that anxiolytic drugs produce their pharmacological effects by enhancing brain gamma-aminobutyric acid (GABA) transmission. During long-term exposure to anxiolytics, brain GABA synapses show evidence of adaptive changes which would tend to reduce the effect of the anxiolytic and restore normal GABA function. Abrupt cessation of anxiolytic treatment might therefore lead to an acute reduction in GABA function; this change could underlie the severe symptoms associated with tranquilliser withdrawal.